Students' interest in school Al-Kautsar Al Akbar Medan supported food security in Northern Sumatera, Indonesia - Ameilia Zuliyanti Siregar; Zulkifli Nasution; Meutia Nauly; Tulus Tulus; Netti Herlina Siregar; Fitri Indira Nauli; Irli Masitah Marpaung; Ichwana Ramli; Mahidin Mahidin; Nasrul Nasrul; Indera Sakti Nasution; Melinda; Muhibuddin (Indonesian Journal of Community Services, 2026)
Agriculture is a vital sector for the economy and food security, especially for Islamic boarding schools (Pesantren) that have limited resources, such as access to water and electricity. Many Islamic boarding schools in remote areas face challenges in achieving economic independence, while available land is not optimally utilized. Therefore, technology-based innovation is needed to optimize existing resources and increase agricultural productivity. The Indonesian Collaborative Community Service (PMKI) USU 2025 aims to select 32 students and teachers during July–October 2025 who demonstrate interest, potential, and a sense of belonging in gardening activities to introduce and implement a smart farming-based agroecosystem in Al Kautsar Al Akbar Islamic Boarding School. Agripreneur activities train participants in suitable cultivation techniques, organic fertilizer production, seed selection, and marketing of organic fertilizer products to the community. Smart farming systems enable more precise and strategic decision-making through the use of sensors and Internet of Things (IoT)-based collected data.